Discovery and preclinical characterization of novel small molecule TRK and ROS1 tyrosine kinase inhibitors for the treatment of cancer and inflammation. - Ramesh Narayanan (Public Library of Science (PLoS), 2013)
Receptor tyrosine kinases (RTKs), in response to their growth factor ligands, phosphorylate and activate downstream signals important for physiological development and pathological transformation. Increased expression, activating mutations and rearrangement fusions of RTKs lead to cancer, inflammation, pain, neurodegenerative diseases, and other disorders. Activation or over-expression of ALK, ROS1, TRK (A, B, and C), and RET are associated with oncogenic phenotypes of their respective tissues, making them attractive therapeutic targets. Cancer cDNA array studies demonstrated over-expression of TRK-A and ROS1 in a variety of cancers, compared to their respective normal tissue controls. We synthesized a library of small molecules that inhibit the above indicated RTKs with picomolar to nanomolar potency. The lead molecule GTx-186 inhibited RTK-dependent cancer cell and tumor growth. In vitro and in vivo growth of TRK-A-dependent IMR-32 neuroblastoma cells and ROS1-overexpressing NIH3T3 cells were inhibited by GTx-186. GTx-186 also inhibited inflammatory signals mediated by NFκB, AP-1, and TRK-A and potently reduced atopic dermatitis and air-pouch inflammation in mice and rats. Moreover, GTx-186 effectively inhibited ALK phosphorylation and ALK-dependent cancer cell growth. Collectively, the RTK inhibitor GTx-186 has a unique kinase profile with potential to treat cancer, inflammation, and neuropathic pain.